Braided Rivers 2006
DOI: 10.1002/9781444304374.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Response of the Brahmaputra–Padma–Lower Meghna River System to the Assam Earthquake of 1950

Abstract: Sediment rating curves Chapter 6 Conceptual model 174 6.1 Introduction 6.2 Celerity of the disturbance in a riverbed 6.3 Changes in the Independent Variables 6.3.1 Changes in the flow regime 6.3.2 Changes in bed sediment size 6.3.3 Changes in the sediment regime 6.4 Changes in the Dependent Variables 6.4.1 Changes in bed elevation 6.4.2 Changes in width 6.4.3 Changes in braiding intensity 6.4.4 Phase lags in the observed morphological changes 65 Development of the conceptual process-response model.. 201 6.5.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 93 publications
(488 reference statements)
1
54
0
Order By: Relevance
“…An adjustment to one bar, bifurcation, or branch initiates a sequence of adjustments in the downstream direction through (1) asymmetrical division of discharge and sediment transport over bifurcation branches, (2) of the bar along the dominant branch, and (3) change in approaching flow towards the successive bifurcation. The celerity of this propagating wave was several orders of magnitude larger than the migration rates of the bars themselves, which is in agreement with the observations of Sarker and Thorne (2006) and with theory. A crucial driver behind the propagation was found to be the asymmetrical reshaping of mid-channel bars in response to an unequal division of discharge and sediment over the directly upstream-located bifurcations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An adjustment to one bar, bifurcation, or branch initiates a sequence of adjustments in the downstream direction through (1) asymmetrical division of discharge and sediment transport over bifurcation branches, (2) of the bar along the dominant branch, and (3) change in approaching flow towards the successive bifurcation. The celerity of this propagating wave was several orders of magnitude larger than the migration rates of the bars themselves, which is in agreement with the observations of Sarker and Thorne (2006) and with theory. A crucial driver behind the propagation was found to be the asymmetrical reshaping of mid-channel bars in response to an unequal division of discharge and sediment over the directly upstream-located bifurcations.…”
Section: Discussionsupporting
confidence: 80%
“…For the initial conditions, the predicted celerity, c, is around 17 km year −1 . Sarker and Thorne (2006) estimated the celerity in the Brahmaputra at 16 to 32 km year −1 , and compared this with the propagation celerity observed in the field after an enormous earthquake. They observed different propagation celerities for different types of responses: around 50 km year −1 for bed level change, which is much faster than the bars; 10 to 37 km year −1 for width adaptation; and 13 km year −1 for braiding index adaptation.…”
Section: Methods For Analysismentioning
confidence: 99%
“…The threat started to take effect in the late 18th century, taking many years according to many studies, and finally the Brahmaputra started to divert the flow through the Jennai River (Coleman, 1969;Morgan and McIntire, 1959;Sarker, 2009). However, based on Rennell's map of 1776 and modern maps, Bristow (1999) argued that the Jennai River was located to the east of the town of Dewanganj (in the Jamalpur district) before the avulsion but that after the avulsion the Brahmaputra occupied a channel west of Dewanganj.…”
Section: Century-scale Delta Developmentmentioning
confidence: 99%
“…Sarker et al (2011) indicated that sediment generated by the 1950 earthquake, which was transported through the Brahmaputra, caused huge sedimentation in the Meghna estuary. The fine fraction of sediment rushed into the estuary within a few years, whereas the coarse fraction (fine sand) propagated downstream as a sediment wave and took nearly five decades to complete its journey to the bay (Sarker, 2009;Sarker and Thorne, 2006). Sarker, Akter, and Rahman (2013) indicated that the rate of land reclamation in the Meghna estuary was mainly a result of sediment carried to the estuary, which was generated after the 1950 Assam earthquake.…”
Section: Role Of Assam Earthquake 1950mentioning
confidence: 99%
See 1 more Smart Citation